Recovery pattern following bimaxillary orthognathic surgery: Differences between sexes. Issue 1 (January 2019) - Song, In-Seok; Choi, Jimi; Baik, Un-Bong; Ryu, Jae-Jun; Lim, Jong-Woo; Choi, Young-Jun; Lee, Ui-Lyong
Abstract: The investigators hypothesized there would be differences between the sexes in recovery pattern following bimaxillary orthognathic surgery as measured by patient responses at 5 weeks postprocedure. A total of 378 participants underwent bimaxillary orthognathic surgery with or without adjunctive procedures. Participants received questionnaires 5 weeks postsurgery when they visited the outpatient clinic. The questionnaires include variances in surgical factors by sex, and postoperative symptoms which were most difficult to tolerate experiences by sex, respectively. Females were more likely to undergo malarplasty (zygoma reduction) than were male participants ( P = <.001), and they required larger maxillary setback than did male participants ( P = .003). Malarplasty was significantly correlated with ear fullness in total and female participants (p-value .018, .016, respectively). Snoring is significantly associated with malarplasty and segment osteotomy procedure without gender predominance (p-value = .026, .028, respectively). Over half of participants complained of nasal congestion (55.6%), followed by swelling (29.3%), pain (15.4%), breathing difficulty (10.6%). In conclusion, males and females showed different patterns of postoperative recovery following bimaxillary orthognathic surgery.